Hutang Luar Negeri Indonesia Ditinjau Dari Perspektif Ekonomi Islam - Faishol Lutfi (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2019)
There are so many interesting phenopenone if we discuss of Indonesian economy especially at monetary sector. Foreign debt is one of several popular problem on developing countries like Indonesia. It is one of practice solution about saving debt to maintain the development process. The aim of this research is to analyse Indonesian foreign debt and How Islamic perspective views it. Analytical method used in this research is literature study. We used secondary data taken from BI, BPS, Kemenkeu, etc. The result of this research shows that foreign debt will be a boomerang when not properly managed by the government. In some cases, Indonesia's current foreign debt conditions do not conform to the norms taught by Islam. The implication is that the government needs a re-review of foreign debt to be more in line with Islamic norms which put forward the side of maslahat